In Zeiten des Strukturwandels Regionen in Deutschland besser fördern - Robert Grundke; Enes Sunel (Wirtschaftsdienst, 2025)
Die regionalen Unterschiede in Deutschland haben abgenommen, sind aber nach wie vor beträchtlich. Und sie könnten sich im Zuge der ökologischen und digitalen Transformation wieder vergrößern. Drei Dinge sollten deshalb getan werden: Erstens, die Regionalfördermaßnahmen und andere Maßnahmen mit regionaler Wirkung besser koordinieren. Zweitens, die finanziellen und administrativen Kapazitäten der Kommunen verbessern. Und drittens, die Energie- und Digitalinfrastruktur zügig ausbauen. – – Regional disparities in Germany have decreased but still remain considerable. And they could widen again as a result of the ecological and digital transformation. Regional economic development should be better coordinated in the future in order to increase its effectiveness. This could be done, in particular, with the federal government's extensive earmarked funding, e.g. in areas such as infrastructure, innovation and industrial policy. Furthermore, the financial and administrative capacities in many municipalities need to be improved in order to resolve infrastructure backlogs and cope with structural changes. In addition to increasing property tax revenues, municipalities should receive compensation when legislative changes at the federal level affect their budgets. Greater cooperation and the bundling of tasks at the municipal level can increase spending efficiency and administrative capacity, which is particularly important in the context of increasing staff shortages.
Keywords: H20; H70; O20; R10; R50; 330